2007
DOI: 10.1186/bf03352018
|View full text |Cite
|
Sign up to set email alerts
|

Seismic velocity variations on the San Andreas fault caused by the 2004 M6 Parkfield Earthquake and their implications

Abstract: mainshock show a peak of an approximately 2.5% decrease in seismic velocity at stations within the fault zone, most likely due to the co-seismic damage of fault-zone rocks during dynamic rupture of this earthquake. The damage zone is not symmetric; instead, it extends farther on the southwest side of the main fault trace. Seismic velocities within the fault zone measured for later repeated aftershocks in the following 3-4 months show an approximate 1.2% increase at seismogenic depths, indicating that the rock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 59 publications
3
36
0
Order By: Relevance
“…Because crack density decreases with depth and lithostastic pressure increases with depth, it is likely to occur in the first 5 km, where surface waves are also very sensitive. Additional evidence supporting crack activity during the Parkfield earthquake comes from Li et al [2007] who reported the occurrence of significant rock damage and healing related to the mainshock of the Parkfield earthquake and Rubinstein and Beroza [2005] who explained their observed travel-time delays in the S coda before and after the Parkfield earthquake by the opening of cracks during the mainshock. These types of observations are not limited to the SAF at Parkfield.…”
Section: Discussionmentioning
confidence: 99%
“…Because crack density decreases with depth and lithostastic pressure increases with depth, it is likely to occur in the first 5 km, where surface waves are also very sensitive. Additional evidence supporting crack activity during the Parkfield earthquake comes from Li et al [2007] who reported the occurrence of significant rock damage and healing related to the mainshock of the Parkfield earthquake and Rubinstein and Beroza [2005] who explained their observed travel-time delays in the S coda before and after the Parkfield earthquake by the opening of cracks during the mainshock. These types of observations are not limited to the SAF at Parkfield.…”
Section: Discussionmentioning
confidence: 99%
“…Suggestions of trapping structures at the SJFZ and other locations that extend to the bottom of the seismogenic zone (e.g. Li & Vernon 2001;Li et al 2004Li et al , 2007 were not supported by more quantitative subsequent analyses using larger data sets (e.g. Peng et al 2003;Yang & Zhu 2010).…”
Section: Discussionmentioning
confidence: 99%
“…With data from a very dry region in Chile, Richter et al (2014) derived a model for the annual variations based on thermally induced stress described in more detail in Section 3.1.1. Velocity drops after large earthquakes followed by a slow recovery were detected by Rubinstein & Beroza (2004a), Li et al (2007), Brenguier et al (2008a), Wegler et al (2009), Nakata & Snieder (2011), Takagi et al (2012), Hobiger et al (2012), Richter et al (2014) and other authors. In particular, Richter et al (2014) showed that the amplitude of the velocity drop after an earthquake is proportional to the local peak ground acceleration (pga).…”
mentioning
confidence: 96%
“…With a study of repeated earthquakes and explosions before and after the 2004 Parkfield earthquake, Li et al (2007) observed a decrease in the size of the velocity changes measured in the fault zone with a decrease in slip during the main shock. As mechanism they suggested coseismic damage of fault-zone rocks during the rupture of this earthquake.…”
Section: Transient Velocity Changesmentioning
confidence: 99%